2015
DOI: 10.1515/rjim-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in inflammatory bowel disease

Abstract: Inflammatory bowel diseases are chronic afflictions, characterized by active and remission periods. Inflammation is the most common type of response that the human body uses as a defense mechanism against aggressors from the environment. The frequency and degree of inflammation depends on the size of the affected tissues. The gastrointestinal tract is, by far, the most susceptible tissue to inflammatory responses, because of its constant exposure to various antigenic, mutagenic and toxic factors. In inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 71 publications
(65 reference statements)
0
49
0
1
Order By: Relevance
“…Plumericin (3 mg/kg, i.p.) 39 Levels of proinflammatory enzymes such as iNOS or COX-2 are also elevated in IBD as a result of the intestinal inflammation. Data are expressed as the mean ± SEM of 10 mice for each group.…”
Section: Discussionmentioning
confidence: 99%
“…Plumericin (3 mg/kg, i.p.) 39 Levels of proinflammatory enzymes such as iNOS or COX-2 are also elevated in IBD as a result of the intestinal inflammation. Data are expressed as the mean ± SEM of 10 mice for each group.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-1 family is expressed throughout the GI tract where it has been associated with autoimmune and chronic inflammatory diseases [68,69]. The IL-1 family of cytokines are predominately produced by stimulated macrophages, monocytes, fibroblasts, and dendritic cells, but can also be produced by lymphocytes and epithelial cells [70,71]. In the gut, various family members including IL-1α, IL-1β, IL-18, IL-33 and IL-37 are produced directly by IECs [72].…”
Section: Il-1 -Driver Of Inflammationmentioning
confidence: 99%
“…In the gut, various family members including IL-1α, IL-1β, IL-18, IL-33 and IL-37 are produced directly by IECs [72]. IL-1α and IL-1β bind to two IL-1 receptor types; IL-1 receptor type I and IL-1 receptor type II [71,73]. Signaling is regulated by the IL-1 receptor antagonist (IL-1Ra), which competitively binds the IL-1RI.…”
Section: Il-1 -Driver Of Inflammationmentioning
confidence: 99%
“…It has been previously reported that inflammatory cytokines are mainly derived from immune cells such as monocyte/macrophages and dendritic cells (28) and miR-155 regulates inflammatory cytokine production in tumor-associated macrophages (29). To determine whether miR-155 expression is involved in the secretion of inflammatory cytokines in macrophages, we detected the mRnA of IL-1β and TNF-α and their protein levels in supernatant by RT-PCR and ELISA respectively.…”
Section: S100a8-induced Upregulation Of Mir-155 Enhances the Secretiomentioning
confidence: 99%